1993
DOI: 10.1139/l93-087
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent slenderness ratio for built-up members

Abstract: Built-up struts that buckle about an axis perpendicular to the plane of the connectors should be treated as a "built-up" member as opposed to a "simple" member. This mode of buckling causes shear and moments in the connectors which deform the connectors. These deformations increase the lateral deformation of the member and hence affect the load-carrying capacity. To account for this effect the easiest method is to use an equivalent slenderness ratio such as the one included in the Canadian Standard. This note … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The investigation highlighted the design of built-up battened double-angle columns. Temple and Elmahdy [7,8] discussed the buckling mode of built-up carbon steel columns. In the study [7], the authors proposed a brief derivation of an equivalent slenderness ratio equation and its applicability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation highlighted the design of built-up battened double-angle columns. Temple and Elmahdy [7,8] discussed the buckling mode of built-up carbon steel columns. In the study [7], the authors proposed a brief derivation of an equivalent slenderness ratio equation and its applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Temple and Elmahdy [7,8] discussed the buckling mode of built-up carbon steel columns. In the study [7], the authors proposed a brief derivation of an equivalent slenderness ratio equation and its applicability. While the study [8] showed that nondimensional slenderness ratio of main column components between connection points had a significant effect on the column strength and buckling behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Zahn and Haaijer [12] determined the number of connectors and the accompanying design strength for double-angle columns. Temple and Elmahdy [13] investigated the buckling mode of built-up member. Their paper also shows the derivation of the equivalent slenderness ratio equation and its applicability.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Substantial investigation on built-up columns has been mostly focused on the in-depth study of conventional built-up columns, of which the branch components are channel-section and I-section [13][14][15][16][17]. Detailed research was conducted by Lue [18] and a comparison of slenderness ratios specified in various design codes was provided.…”
Section: Introductionmentioning
confidence: 99%